The Influence of Facilities, Service Quality, and Price Perception on Customer Loyalty at Dejavu Billiard Denpasar - Hapsari, Putu Indah; Amunutur, Clarita Bunga; Kusuma, A. A. Made Indra Wijaya (Journal of Governance, Taxation and Auditing, 2026)
The development of Micro, Small, and Medium Enterprises (MSMEs), particularly in the entertainment sector, requires business actors to compete by providing adequate facilities and high-quality services in order to maintain customer loyalty. Dejavu Billiard Denpasar experienced a decline in the number of visits from 280 visits in 2023 to 220 visits in 2024, representing a decrease of 21.4%, which indicates low customer loyalty. This decline is presumed to be influenced by inadequate facilities, service quality especially in the tangible (physical evidence) aspect and price perceptions that are considered not fully comparable to the benefits received by customers. In addition, inconsistencies in previous research findings (research gap) regarding the influence of these three variables on customer loyalty provide an important basis for conducting this study. The sample used in this research consisted of 96 respondents drawn from customers of Dejavu Billiard Denpasar. Data were collected through observation, interviews, and surveys. The collected data were analyzed using multiple linear regression analysis. The results indicate that facilities have a positive and significant effect on customer loyalty at Dejavu Billiard Denpasar. Service quality also has a positive and significant effect on customer loyalty. Likewise, price perception has a positive and significant effect on customer loyalty. Simultaneously, facilities, service quality, and price perception have a positive and significant effect on customer loyalty at Dejavu Billiard Denpasar.